KNOWLEDGE, ATITTUDE AND PRACTICES TOWARDS PREVENTION AND CONTROL OF DIARRHEA DISEASES AMONG CHILDREN UNDER 5 YEARS AT PEADIATRIC WARD RAKAI GENERAL HOSPITAL RAKAI DISTRICT. A CROSS SECTIONAL STUDY. - NALUYIMA, PHIONAH; ODIWUOR , OTIENO JOASH (Student's Journal of Health Research Africa, 2024)
Background The broad objective was to examine the knowledge attitude and practices of caretakers towards the prevention and control of diarrhea among children under five years at the pediatric ward of Rakai Hospital in Rakai district. Methodology The cross-sectional study was carried out on all caretakers of children less than five years at Rakai General Hospital. The Questionnaire was used to collect data and was analyzed using a tally; the sample size of 62 respondents also was analyzed using tables and pie charts. Results The study revealed that majority 48.3% of the respondents had good knowledge on contaminated food/water as the cause of diarrhea in children under five years, 87.1% had good knowledge on general weakness, failure to feed, irritability, vomiting everything as the consideration to their children for treatment, 18% of the respondents had poor knowledge on treatment of diarrhea at home, 20% respondents had poor knowledge on what is needed to make ORS, 18% respondents had poor knowledge on how to prevent diarrhea in their children, 61.8% respondents poor attitude on exclusive breastfeeding. Conclusion The study concluded that mothers had good knowledge of the causes of diarrhea among children under five years and identified the danger signs. 18.0% had poor knowledge of how to treat diarrhea at home, the requirements to make ORS and how to prevent diarrhea in their children. Recommendation Consequently, the study suggests that caregivers should get ongoing health education on how to treat diarrhea at home, what's needed to create ORS, how to stop diarrhea in children, and how to breastfeed children who have diarrhea.